2008
DOI: 10.1037/0012-1649.44.2.422
|View full text |Cite
|
Sign up to set email alerts
|

Combining group-based trajectory modeling and propensity score matching for causal inferences in nonexperimental longitudinal data.

Abstract: A central theme of research on human development and psychopathology is whether a therapeutic intervention or a turning-point event, such as a family break-up, alters the trajectory of the behavior under study. This article describes and applies a method for using observational longitudinal data to make more transparent causal inferences about the impact of such events on developmental trajectories. The method combines 2 distinct lines of research: work on the use of finite mixture modeling to analyze developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
98
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 58 publications
0
98
0
1
Order By: Relevance
“…or three (n=50; Bongers et al, 2004;Broidy et al, 2003;Campbell et al, 2010;Cohen et al, 2010b;Constantine et al, 2010;Coté et al, 2007;Di Giunta et al, 2010;D'Unger et al, 2002;Fontaine et al, 2008; Freilburger, Marcum, Iannacchione, & Higgins, 2012;Haviland et al, 2008;Higgins, Bush, et al, 2010;Higgins, Piquero, & Piquero, 2011;Jennings, Maldonado-Molina, et al, 2010;Jones & Nagin, 2007;Jones et al, 2001;Kreuter & Muthén, 2008;Lacourse et al, 2003;Latendresse et al, 2011;McDermott & Nagin, 2001;Nagin, 1999;Reef et al, 2011;Saunders, 2010;Tewksbury & Jennings, 2010;Tremblay et al, 2004;Underwood et al, 2009;van Domburgh et al, 2009;van Lier et al, 2009;Vaughn et al, 2009) trajectory groups.…”
mentioning
confidence: 96%
“…or three (n=50; Bongers et al, 2004;Broidy et al, 2003;Campbell et al, 2010;Cohen et al, 2010b;Constantine et al, 2010;Coté et al, 2007;Di Giunta et al, 2010;D'Unger et al, 2002;Fontaine et al, 2008; Freilburger, Marcum, Iannacchione, & Higgins, 2012;Haviland et al, 2008;Higgins, Bush, et al, 2010;Higgins, Piquero, & Piquero, 2011;Jennings, Maldonado-Molina, et al, 2010;Jones & Nagin, 2007;Jones et al, 2001;Kreuter & Muthén, 2008;Lacourse et al, 2003;Latendresse et al, 2011;McDermott & Nagin, 2001;Nagin, 1999;Reef et al, 2011;Saunders, 2010;Tewksbury & Jennings, 2010;Tremblay et al, 2004;Underwood et al, 2009;van Domburgh et al, 2009;van Lier et al, 2009;Vaughn et al, 2009) trajectory groups.…”
mentioning
confidence: 96%
“…They found that grade retention seems to exacerbate physical aggression in the low- and high-declining trajectory groups but has no apparent effect on the physical aggression of the extreme groups - the lows and the chronics. The model extension allowing for this sort of analysis is developed in chapter 7 of Nagin [1] (see also Haviland et al [17,18] for a discussion of the use of propensity score matching in combination with GBTM in making causal inferences about the effect of life events and interventions on developmental trajectories).…”
Section: An Illustration Of Gbtmmentioning
confidence: 99%
“…7 7 In fact, Haviland et al have utilized GBTM to draw causal inferences in the context of non-experimental, observational study by first examining the developmental patterns prior to the treatment and testing how such prior growth trajectories condition the effect of treatment (Haviland and Nagin 2005). Later, they used the estimated prior developmental trajectories of outcome measures in combination with propensity scores for experiencing treatment to better achieve the balance between treatment and control groups (Haviland and Nagin 2007;Haviland et al 2008). In doing so, they demonstrated how GBTM can also be used to identify potentially heterogeneous treatment effects that may meaningfully vary depending on the prior developmental trajectories.…”
Section: Level-1 Modelmentioning
confidence: 96%